Extent of untouchability and pattern of discrimination/ Sheo Kumar Lal and Umed Raj Nahar - "Lal, Sheo Kumar" (New Delhi, 1990)
All these efforts resulted in formulating policies to ensure them freedom and social justice after India became Indepen dent. No doubt, there has been some change in practice of untouchability in public places but there does not seem to have been major change in the general attitude of privileged classes. Organised efforts backed by legislative and executive action, and educational expansion may hopefully mitigate the evil practice of untouchability-a practice which is a blot on our secular principles. This book has effectively dealt with these vexed problems of our social life.
Keywords: Untouchables